Siliciclastic cave or diamond mine? Multiapproach investigation in Igatu Village, Chapada Diamantina, northeastern Brazil - Parra, Raphael; Pereira, Ricardo; Vieira, Leonardo; Maia, Rubson (International journal of speleology, 2025)
The territory around Igatu, as that of many villages in southeastern Chapada Diamantina (Bahia, Brazil), was deeply modified by diamond mine activity. Caves were special targets for miners, since they can act as diamond-bearing sediment traps, and the Canal da Fumaça Cave was one of the most important and rich of them. The question that arises is whether the formation is a natural cave or an artificial diamond mine. In order to answer this question, we developed speleological and geological studies with detailed cave surveys, remote sensing and field measurements for structural analysis, optical and electronic microscope for petrographic characterization, as well as chemical (XRF) and mineralogical (XRD) analyses. Data indicate that structures associated to strike-slip faults play a fundamental role in conduit opening and ruiniform relief formation, acting as preferential weathering fronts. Petrological description suggests that chemical attack on quartz-metasandstone occurs mainly in the phyllosilicate (pyrophyllite + kaolinite) matrix, which is more soluble in acid conditions, and secondarily along the quartz grains. The phantomization reduces grain cohesion promoting piping processes that remove the loose quartz grains mechanically. However, anthropogenic impact during mining activity was strong, leaving several marks, such as constructions, excavations, and areas of detonation that certainly increased cave dimensions. Finally, we propose a model for natural and anthropogenic evolution of the Canal da Fumaça Cave.